Marital Property in Indonesia - Akbar, Wahyu; Kurniawan, Rahmad (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2023)
This study examines the position of marital assets in the law and customary law of the Dayak ngaju in the Indonesian legal system. Marital assets in the 1974 Marriage Law and KHI are legal products originating, one of them from Customary Law, which still leaves problems in its implementation. As a result, judges differ in decisions in settling marital assets in Indonesia. This paper applies a type of normative research. Besides that, it also uses the library research method, which examines the literature analyzed qualitatively using a statutory approach and a conceptual approach to Islamic Economic Law. The results of this study indicate that UUP marriage can be reviewed, one of which can be sourced from customary law, especially the institutionalized Dayak Ngaju. Marital assets should provide economic guarantees for women's and children's futures through the distribution of marital assets.